Social interactive television immersive shared experiences and perspectives - Cesar, Pablo; Geerts, David; Chorianopoulos, Konstantinos 1975- (Information Science Reference, 2009)
"This book discusses the advent of social interactive television with its complex opportunities and challenges for media researchers and others today" - Provided by publisher
Includes bibliographical references and index
Keywords: Interactive television; Interaktives Fernsehen; Aufsatzsammlung